The Relationship of Perceived Usefulness (PU) and Attitude Towards Using (ATU) in Students of Scola Users Learning Biology at Dedikasi Edukasi Kualiva Senior High School - Aulia Hafifah; Relsas Yogica; Heffi Alberida; Helsa Rahmatika (LP2M STIT Palapa Nusantara, 2023)
The material on Biology subjects is broad and abstract concepts, so that online biology learning media such as e-learning are needed. Based on observations, Dedekadasi Edukasi Kualiva (DEK) SHS is one of the private schools in Padang that uses Scola as an e-learning platform in biology learning even though learning is done offline. However, it has never been analyzed the success of the use of Scola in biology learning in high school deck with any instrument so it is not known the relationship of PU with ATU in students using Scola biology learning in DEK high school. The purpose of this study was to determine the relationship of PU with ATU in students using Scola biology learning at DEK high school. This type of research is descriptive correlation with quantitative approach conducted at DEK high school. The sample consisted of 48 students, in Class X Phase E, XI science, and XII science, with sampling techniques, namely total sampling techniques. Analysis of the data used is Pearson product moment correlation test and t test after knowing the normal distribution of data. The results of the study using Pearson product Moment correlation test showed a positive correlation with the value of r = 0.7587 (strong correlation) and the value of the count (7.899) > table (1.679). These results indicate that the hypothesis is accepted. Therefore, PU has a significant positive relationship to the Attitude towards Using (ATU) in students who use Scola biology learning at DEK high school.